2020
DOI: 10.2174/1573406415666190613094433
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Biological Evaluation of Anti-tuberculosis Agents based on Bedaquiline Structure

Abstract: Background: Bedaquiline is a novel anti-tuberculosis drug that inhibits Mycobacterial ATP synthase. However, studies have found that bedaquiline has serious side effects due to high lipophilicity. Recently, the complete structure of ATP synthase was first reported in the Journal of Science. Objective: The study aimed to design, synthesise and carry out biological evaluation of antituberculosis agents based on the structure of bedaquiline. Methods: The mode of action of bedaquiline and ATP synthase was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…More recently, it was reported that bedaquiline analogs and other compounds binding to the bedaquiline binding site display more potent antituberculosis activity and/or less toxicity to mammals than bedaquiline. 83,84) These inhibitors could be potential candidates for antidental caries agents.…”
Section: Inhibitors Of Bacterial Proton Pumping Atpasesmentioning
confidence: 99%
“…More recently, it was reported that bedaquiline analogs and other compounds binding to the bedaquiline binding site display more potent antituberculosis activity and/or less toxicity to mammals than bedaquiline. 83,84) These inhibitors could be potential candidates for antidental caries agents.…”
Section: Inhibitors Of Bacterial Proton Pumping Atpasesmentioning
confidence: 99%
“…181-182 1C. (S)-2-amino-N-(3-(N-cyclohexyl-N-ethylsulfamoyl)phenyl)-4-methylpentanamide (22). To a solution of (S)-2-Boc-amino-N-(4-(N-(furan-2-ylmethyl)sulfamoyl)phenyl)-4-methylpentanamide (0.6 g, 0.0013 mol) in DCM, TFA (0.45 g, 0.004 mol) was added at room temperature and the mixture was stirred for 4 h. Later, it was washed with saturated NaHCO 3 solution and followed by brine solution.…”
Section: Synthesesmentioning
confidence: 99%
“…In related literature reports, it has been observed that the heterocyclic structure can generate hydrogen bonds with protein receptors, thereby increasing the activity of compounds. [21][22][23] Based on the key role of leucine and benzamide in various antibacterial drugs, we designed and synthesized a series of new leucine aniline derivatives. We hope to have a good structure-activity relationship.…”
Section: Introductionmentioning
confidence: 99%